Theoretical Aspects of Thin Film Optical Spectra: Underlying Models, Model Restrictions and Inadequacies, Algorithms, and Challenges - Olaf Stenzel; Steffen Wilbrandt (Applied Sciences)
Any calculation of thin film optical spectra requires the formulation of certain model assumptions. In general, those model assumptions concern geometrical features as well as material properties. We review important facets of the thin film optics’ “standard model” that provides the basis of generally accepted relevant modern spectra calculation routines. Moreover, we discuss phenomena arising when certain model assumptions are violated. Examples are provided by the Goos–Hänchen shift, the polarization leakage, interaction with partially coherent light, rough surfaces, as well as the emergence of thickness-dependent, time-dependent, or non-linear optical material parameters. Corresponding challenges in coating characterization and design are discussed, and future prospects are identified.